Vibration Reduction Performance of Structures with Viscous Dampers under Near-Field Earthquakes - Jianguang Lin (Advances in Civil Engineering)
Near-field pulse-type ground motions (NPGMs) are characterized by a high-energy pulse with large peak ground velocities and accelerations and need further studies to confirm whether structures with viscous dampers (VDs) are still applicable and effective for this type of ground motions. In this article, the vibration reduction performance of structures with VDs under near-field earthquakes is investigated systematically. Displacement and acceleration spectra are developed for a single-degree-of-freedom (SDOF) structure with and without VDs, while these influence factors, such as the nonlinear characteristic of structure, damper supports’ flexibility, and damper parameters, are considered. Additionally, the frequency domain characteristics of NPGM and the energy distribution of a multidegree-of-freedom (MDOF) structure with VDs are discussed to further reveal the action mechanism of NPGM on the structure. It is shown that the structure with VDs shows remarkable seismic reduction effect under the action of near-fault pulse-type earthquake, and the maximum interstorey drift decreased from 0.086 to 0.037 when the structure is equipped with VDs. However, the structure may still be difficult to completely dissipate the high-energy generated by the earthquake pulse with a high pulse period in a short time, which can cause the structure to be damaged or even collapsed in a moment.